2017
DOI: 10.3390/ijms19010100
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Novel Fibrinogen Bβ Chain Mutations in Two Slovak Families with Quantitative Fibrinogen Disorders

Abstract: Congenital fibrinogen disorders are caused by mutations in one of the three fibrinogen genes that affect the synthesis, assembly, intracellular processing, stability or secretion of fibrinogen. Functional studies of mutant Bβ-chains revealed the importance of individual residues as well as three-dimensional structures for fibrinogen assembly and secretion. This study describes two novel homozygous fibrinogen Bβ chain mutations in two Slovak families with afibrinogenemia and hypofibrinogenemia. Peripheral blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…At the end of 2017, novel nonsense variants in afibrinogenemic patients have been reported. In a 28-year-old afibrinogenemic man presenting with mucocutaneous bleeding and blood losses into muscles, joints, and soft tissues, the Gln180Stop “Martin” variant was identified in FGB [ 43 , 44 ]. Naz and colleagues described the novel FGA p.Gln183stop and FGG p.Lys121stop nonsense variants in two afibrinogenemic patients from Pakistan [ 45 ].…”
Section: Afibrinogenemiamentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of 2017, novel nonsense variants in afibrinogenemic patients have been reported. In a 28-year-old afibrinogenemic man presenting with mucocutaneous bleeding and blood losses into muscles, joints, and soft tissues, the Gln180Stop “Martin” variant was identified in FGB [ 43 , 44 ]. Naz and colleagues described the novel FGA p.Gln183stop and FGG p.Lys121stop nonsense variants in two afibrinogenemic patients from Pakistan [ 45 ].…”
Section: Afibrinogenemiamentioning
confidence: 99%
“…In a non-thrombophilic woman, who experienced thrombosis events and miscarriages, Casini and colleagues identified the fibrinogen beta chain p.Gly472Val missense change [ 51 ]. Furthermore, in a 62-year-old hypofibrinogenemic man with a history of venous thromboses, the fibrinogen beta chain p.Tyr368His variant was found [ 43 ]. Protein modeling represents a helpful tool to understand functionality and causality of genetic variants identified in fibrinogen beta chain [ 52 ].…”
Section: Hypofibrinogenemiamentioning
confidence: 99%
“…The pathogenesis at the basis of the paradoxical thrombotic tendency in congenital quantitative fibrinogen disorders is likely multifactorial, depending on exogenous and endogenous risk factors such as genetic thrombophilia, use of fibrinogen concentrate, trauma, immobilization, or pregnancy. The true mechanisms of thrombosis in these patients still remain unexplained [26,45].…”
Section: Pathogenesis and Risk Factors For Thrombosis In Congenital Qmentioning
confidence: 99%
“…3 Paradoxically, thrombosis in both venous and arterial sites are also a typical complication of congenital FIB disorders, in addition to bleeding symptoms. 4,5 In their study, the authors identified 2 novel FIB mutations in 2 Slovak families with quantitative FIB disorders and concluded the development of thrombotic complications was spontaneous since the patient and his son did not receive substitution therapy with the FIB concentrate in the period of their recurrent thromboses manifestation. 5 Due to their specific physiological characteristics, female patients tend to have congenital hypofibrinogenemia/afibrinogenemia, such as spontaneous recurrent abortion, menorrhagia, infertility, antepartum and postpartum hemorrhage, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 In their study, the authors identified 2 novel FIB mutations in 2 Slovak families with quantitative FIB disorders and concluded the development of thrombotic complications was spontaneous since the patient and his son did not receive substitution therapy with the FIB concentrate in the period of their recurrent thromboses manifestation. 5 Due to their specific physiological characteristics, female patients tend to have congenital hypofibrinogenemia/afibrinogenemia, such as spontaneous recurrent abortion, menorrhagia, infertility, antepartum and postpartum hemorrhage, and so on. 6,7 Current studies of congenital hypofibrinogenemia/afibrinogenemia mainly focus on different types of FIB mutations, etiology/pathogenesis, some rare case reports of the diseases, and the relationship of hotspot FIB gene mutations associated with recurrent deep vein thromboses as serious manifestation of thrombotic phenotype.…”
Section: Introductionmentioning
confidence: 99%